IMPLEMENTATION OF TRAIT AND FACTOR THEORY IN IMPROVING CAREER PLANNING FOR CLASS XII STUDENTS OF SMA N 4 SUNGAI PENUH IN THE NEW NORMAL ERA - Tiara Maiza Dianti; Mega Iswari; Daharnis (Yayasan Citra Dharma Cindekia, 2022)
Career counseling guidance is an activity carried out by school counselors in order to help students' career planning, so BK teachers/school counselors need to pay attention to this because it is found in the field that there are students who are still confused in determining the direction of their career which begins with determining the choice of majors in the field. high school program that he will take when he finishes high school. This article, entitled